Perkembangan, Dinamika, dan Tren Penelitian Jurnalisme di Indonesia Periode 2001-2020 - Justito Adiprasetio (Calathu: Jurnal Ilmu Komunikasi, 2022)
After the authoritarian New Order regime collapsed, the study of journalism as a part of communication studies is projected will develop and helps rehabilitating the ecosystem of Indonesian media. However, there is no meta-analysis study that can prove how the development and dynamics of journalism research in Indonesia, especially after more than two decades of the collapse of the New Order. This study, by analyzing 641 journalism studies articles scattered in authoritative scientific publications on communication in Indonesia, in the span of two decades from January 2001 to December 2020, found that Indonesian journalism scholars were enriching literature reference, and were increasingly connected with other scholars. The findings obtained by this study directly refute many accusations that communication studies, especially in the scope of journalism studies in Indonesia, is dominated by positivistic paradigm. During the 2001- 2020 period, although there was an increase in publications that relied on a quantitative approach, it can be seen the dominance of the qualitative approach has not been deterred. The Ministry of Communication and Information Technology of Indonesia in the second position, as the institution with the highest number of scientific article writers after the Universitas Islam Bandung in first place, even surpassing Universitas Padjadjaran and Universitas Diponegoro shows that researchers from government institutions are one of the agents of production and reproduction of journalism knowledge and discourse in Indonesia. Based on keyword trends, the deliberative vision of journalistic research in Indonesia tends not to develop progressively. Keywords: Indonesia, journalism studies, meta-analysis, journalism researc